Arterial hypertension and coronary heart disease in real-world cardiology practice - S. A. Shalnova; A. D. Deev; Yu. A. Karpov (Кардиоваскулярная терапия и профилактика)
Aim. To study association of arterial hypertension (AH) and coronary heart disease (CHD) in real-world cardiology practice. This was the aim of the national PREMIERE Study. Material and methods. The study involved cardiologists from 14 cities of the Russian Federation. During 5 days, every doctor included all consecutive AH and/or CHD male and female patients, aged 18-65 years. During epidemiology phase, 14 075 patients were recruited in the study. For the analysis, 8578 patients were randomly selected, including 3615 (42.1%) males and 4963 (57.9%) females. In all participants, socio-demographic characteristics were measured; complaints, main risk factors (RF), already prescribed therapy, intake regularity and causes of irregular medication intake were registered. Blood pressure and heart rate were measured; electrocardiogram at rest was analyzed. Results. Various CHD forms, including myocardial infarction, effort angina, painless CHD, cardiac arrhythmias, were observed in 72.4% of AH males and 61.2% of AH females. Analyzing RF, associated with AH and CHD, it turned out that 88.5% of AH patients and 95.6% of AH and CHD patients had at least one RF. Education level was a significant determinant for Russian population health, defining awareness, behavioral RF and, therefore, morbidity and treatment attitudes. Persons with higher education more often had cardiovascular disease in family history, lipid profile disturbances, and chronic stress exposure. On the contrary, patients with lower than secondary education level significantly more often smoked, drank alcohol, and had cardiovascular symptoms. Conclusion. Therefore, REMIERE Study results give a chance to assess present cardiology practice, to characterize patients with isolated AH or AH combined with CHD, including complaints and treatment compliance, according to social status and other parameters.